Effect of phosphoric acid on the degradation of human dentin matrix - Tezvergil-Mutluay, A.; Mutluay, M.; Seseogullari-Dirihan, R.; Agee, K. A.; Key, W. O.; Scheffel, D. L S [UNESP]; Breschi, L.; Mazzoni, A.; Tjäderhane, L.; Nishitani, Y.; Tay, F. R.; Pashley, D. H. (SAGE Publications, 2013)
This study determined if dentin proteases are denatured by phosphoric acid (PA) used in etch-and-rinse dentin adhesives. Dentin beams were completely demineralized with EDTA for 30 days. We acid-etched experimental groups by exposing the demineralized dentin beams to 1, 10, or 37 mass% PA for 15 sec or 15 min. Control beams were not exposed to PA but were incubated in simulated body fluid for 3 days to assay their total endogenous telopeptidase activity, by their ability to solubilize C-terminal crosslinked telopeptides ICTP and CTX from insoluble dentin collagen. Control beams released 6.1 ± 0.8 ng ICTP and 0.6 ± 0.1 ng CTX/mg dry-wt/3 days. Positive control beams pre-incubated in p-aminophenylmercuric acetate, a compound known to activate proMMPs, released about the same amount of ICTP peptides, but released significantly less CTX. Beams immersed in 1, 10, or 37 mass% PA for 15 sec or 15 min released amounts of ICTP and CTX similar to that released by the controls (p > 0.05). Beams incubated in galardin, an MMP inhibitor, or E-64, a cathepsin inhibitor, blocked most of the release of ICTP and CTX, respectively. It is concluded that PA does not denature endogenous MMP and cathepsin activities of dentin matrices. © 2013 International & American Associations for Dental Research.
Keywords: bonding; cathepsins; collagen; demineralized; MMPs; 4 aminophenylmercuriacetate; 4-aminophenylmercuriacetate; cathepsin; collagen type 1; collagen type I trimeric cross linked peptide; collagen type I trimeric cross-linked peptide; collagenase; cysteine proteinase inhibitor; dipeptide; drug derivative; enzyme activator; enzyme precursor; ilomastat; leucine; matrix metalloproteinase; matrix metalloproteinase inhibitor; n [n (3 carboxyoxirane 2 carbonyl)leucyl]agmatine; peptide; peptide hydrolase; phenylmercuric acetate; phosphoric acid; thiol reagent; dentin; drug antagonism; drug effect; enzymology; human; materials testing; protein denaturation; time; Cathepsins; Collagen Type I; Collagenases; Cysteine Proteinase Inhibitors; Dentin; Dipeptides; Enzyme Activators; Enzyme Precursors; Humans; Leucine; Materials Testing; Matrix Metalloproteinase Inhibitors; Matrix Metalloproteinases; Peptide Hydrolases; Peptides; Phenylmercuric Acetate; Phosphoric Acids; Protein Denaturation; Sulfhydryl Reagents; Time Factors